Perancangan Sistem Informasi Penilaian Kinerja Karyawan Berbasis Web dengan Keamanan Enkripsi di PT. Brahma Bina Bakti Mill - Aditiya Eka Saputra; Efitra (Jurnal Komputer Teknologi Informasi Sistem Komputer (JUKTISI), 2026)
Employee performance appraisal plays an essential role in improving the quality of human resources and supporting strategic decision-making within organizations. However, manual performance evaluation processes often lead to problems such as data entry errors, delayed reporting, and inadequate data security. This study aims to design a web-based employee performance appraisal information system equipped with a data encryption feature to protect sensitive information at PT. Brahma Bina Bakti Mill. The system was developed using the Rapid Application Development (RAD) method with an iterative approach, while the design process employed Unified Modeling Language (UML). The system was built using the CodeIgniter framework, the PHP programming language, and a MySQL database. System testing was conducted using the Blackbox Testing method to ensure that all functionalities operated as intended. The results indicate that the developed system improves efficiency in performance assessment processes, maintains the confidentiality of appraisal data through encryption, and enables real-time reporting for decision-making.